Attachment Representations of Psychology Candidates via the Birds Nest Drawing Test: A Mixed-Methods Approach - Demir, Volkan; Akoglu, Bahar; Tansel, Bulent (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2025)
This study aimed to explore the attachment representations of psychology candidates in the context of social and educational development. A mixed-method design was used, combining the Three-Dimensional Attachment Scale for quantitative data and the Bird’s Nest Drawing Test for qualitative insights. Participants were 122 senior-year psychology students. No significant correlation was found between drawing scores and attachment subscales. However, many drawings included symbols such as parent and baby birds, eggs, and realistic coloring, often with nests placed on trees, cliffs, or hands—suggesting emotional needs for safety and care. Green, while generally symbolizing growth, appeared infrequently. Occasionally, symbols like the sun or animals suggested hope or emotional ambiguity. Content analysis revealed two themes: a “positive” theme reflecting family warmth and support, and a “negative” theme indicating anxiety and insecurity. These results offer symbolic insight into how future mental health professionals express attachment, highlighting emotional development and their relational understanding.